Viability and collagen secretion by fibroblasts on titanium surfaces with different acid-etching protocols - Vilton Zimmermann de Souza; Rafael Manfro; Júlio César Joly; Carlos Nelson Elias; Daiane Cristina Peruzzo; Marcelo Henrique Napimoga; Elizabeth Ferreira Martinez (SpringerOpen, 2019)
Abstract Background From the consolidation of surface treatments of dental implants and knowledge on the cellular mechanisms of osseointegration, studies have highlighted the importance of a connective tissue seal against the implant to prevent contamination from the oral environment and consequent biofilm formation. Objective This in vitro study aimed to evaluate whether different titanium surface treatments using acid solutions promoted an increase in collagen secretion, proliferation, and viability of fibroblasts. Material and methods Commercially pure grade-4 titanium disks (6 × 2 mm) were treated with different acid solutions (hydrochloric, nitric, and sulfuric) for 20 and 60 min, respectively, obtaining mean surface roughness of 0.1 to 0.15 μm and 0.5 to 0.7 μm. Human fibroblasts were seeded onto different surfaces and assessed after 24 h, 48 h, and 72 h for cell proliferation and viability using Trypan blue staining and MTT, respectively, as well as the secretion of type I collagen on to such surfaces using ELISA. Machined titanium surfaces were used as controls. Data were statistically analyzed using one-way ANOVA and Fisher's LSD test for multiple comparisons, adopting a significance level of 5%. Results No significant difference was observed in cell proliferation for the different surfaces analyzed. Cell viability was significantly lower on the machined surface, after 48 h, when compared to the groups treated with acid for 20 or 60 min, which did not differ from each other. The expression of type I collagen was lowest on the acid-treated surfaces. Conclusion The results showed that the acid treatment proposed did not promote fibroblast proliferation and viability nor favor type I collagen synthesis.